(untitled) (International Journal of Engineering and Computer Science, 2014)
Wireless sensor networks is a self-configured network means any node can join it or leave it at any time. it is a self-healing and self-organizing. Self-healing networks allow nodes to reconfigure their link associations and find other pathways around powered-down nodes or failed nodes. Self-organizing allows a network automatically join new node without the need for manual interference. In this paper, we are using actor nodes to solve energy hole problem so that we can reduce energy consumption and can enhance throughput of network.